2021
DOI: 10.3390/brainsci11081019
|View full text |Cite
|
Sign up to set email alerts
|

Neurosurgical Management and Outcome Parameters in 237 Patients with Spondylodiscitis

Abstract: Surgical treatment of spondylodiscitis allows for rapid mobilization and shortens hospital stays, which makes surgical treatment the first-line therapy. We aim to describe our experiences with operative treatment on spondylodiscitis and to determine the parameters that are important in the prediction of outcomes. A retrospective review identified 237 patients who were operatively treated for spondylodiscitis in our institution between January 2010 and December 2018. Clinical data were collected through review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
6

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 56 publications
(97 reference statements)
2
21
0
6
Order By: Relevance
“…Madhavan et al, 33 in a systematic review of 212 patients with spondylodiscitis and end-stage renal disease, found a rate of 46% of neurological compromise. Similar to our findings, Pojski c et al, 34 in a review of 237 patients, reported 72% preoperative neurological compromise. Of note, 146 patients (61.6%) had epidural abscess at the time of diagnosis in their series.…”
Section: Lessonssupporting
confidence: 92%
“…Madhavan et al, 33 in a systematic review of 212 patients with spondylodiscitis and end-stage renal disease, found a rate of 46% of neurological compromise. Similar to our findings, Pojski c et al, 34 in a review of 237 patients, reported 72% preoperative neurological compromise. Of note, 146 patients (61.6%) had epidural abscess at the time of diagnosis in their series.…”
Section: Lessonssupporting
confidence: 92%
“…In contrast to image-guided mostly fine-needle biopsies proposed by some groups, we perform transpedicular biopsies which allow better sampling due to a wider diameter. In addition, experienced spine surgeons and haptic feedback might further improve sampling, resulting in a diagnostic rate of 64% in our patient collective [28].…”
Section: Discussionmentioning
confidence: 99%
“…Based on large case series, it is known that main microorganisms involved in spondylodiscitis are Mycobacterium tuberculosis and Staphylococcus species. 35,36 Interestingly, in our study, Aspergillus was the most common agent (52%) followed by Staphylococcus species. Vertebral aspergillosis is a relatively rare and often misdiagnosed entity that usually requires long-term antibiotic treatment and surgical treatment.…”
Section: Lessonsmentioning
confidence: 55%